Обґрунтування кінематичних параметрів міжопераційного віброхвильового транспортування сої за її інфрачервоного сушіння - Паламарчук, Ігор Павлович; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Kiurchev, Serhii; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna; Кюрчева, Людмила Миколаївна; Кюрчева, Людмила Николаевна; Kiurcheva, Liudmyla; Стручаєв, Микола Іванович; Стручаев, Николай Иванович; et al. (My University, 2019)
UK: Стаття присвячена проблемі зниження енерговитрат на процес терморадіаційного сушіння насіння сої при максимальному збереженні її вихідних властивостей, шляхом розробки конструктивного оснащення для реалізації міжопераційного транспортування продукції у зоні обробки. Результати експериментальних досліджень виявили ефективність утворення на поверхні гнучкого вантажонесучого органу біжучої або стоячої хвилі, яка забезпечує одночасну реалізацію процесів тепломасообмінної обробки та пошарового перемішування сої. RU: статья посвящена проблеме снижения энергозатрат на процесс сушки сои, путем рассмотрения межоперационной транспортировке к сушке. Приведенные результаты практических исследований с использованием виброволновой инфракрасной сушки. Процесс межоперационной транспортировки сыпучей продукции в установке, позволяет получить необходимую спиралевидную траекторию движения сои при непрерывном перемешивании слоев без применения специализированных механических устройств. EN: The article is devoted to the problem of reducing energy consumption for the process of drying soybeans, by considering the inter-operational transportation to drying. The basic characteristics of vibration are considered: amplitude of oscillation, vibration velocity and vibration acceleration, which influence on interoperative transportation to drying of infrared irradiation of soy. Short-term intense infrared exposure of the surface layer of raw products carries both problems: of their overheating and uneven layer processing. Their promising solution has become the usage of vibrating conveyor and wave techniques. They allow creating favourable conditions for intensifying of the production process and applying effective methods of exposure of its object; implementing continuous process movement; creating general control on dynamic status of the system; minimizing mechanical and thermal damages to the object. Saving and rationalizing the harvest of crops for important crops, skin products, skin conditioners, independent of the structure, the volume of the workplace and other demonstrations. The results of practical research using vibro-infrared drying. Considered a change in the speed of infrared drying of soybean depending on the time at the speed of transportation of products Represented by changes in humidity during the We want to note that the process of transportation is carried out on the peculiarity of the contraction of the vibration-conveyer infrared dryer, which consists of the rollers located on the eccentric shaft.
Обоснование кинематических параметров межоперационной виброволновой транспортировки сои при инфракрасной сушке
Justification of kinematic parameters of inter-operating vibrowave software and for its infrared drying
Keywords: інфрачервоне сушіння; соя; віброхвильове транспортування; коливальна система; амплітуда коливань; віброшвидкість